2007
DOI: 10.1080/00016340601133871
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of density of Langerhans cells in human cervical intraepithelial neoplasia

Abstract: We theorize that the increase in the population of Langerhans cells in areas of CIN 3 could be explained by migration of these cells from adjacent areas without histopathologic alterations in order to act in the restraint of the development of neoplasia; cigarette smoking did not influence this migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 32 publications
2
11
0
2
Order By: Relevance
“…Therefore, the extent of the local immunological depletion determines the progression of lesions. 16,17 In our study, the LC count determined by S100 and CD1a staining unambiguously showed that a fewer number of cells were present in the HIV-seropositive group than in the HIVseronegative group, a finding that is consistent with previous studies in the literature. 18,19 We also found that the anti-S100 antibody stained a greater number of LCs than the anti-CD1a antibody.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, the extent of the local immunological depletion determines the progression of lesions. 16,17 In our study, the LC count determined by S100 and CD1a staining unambiguously showed that a fewer number of cells were present in the HIV-seropositive group than in the HIVseronegative group, a finding that is consistent with previous studies in the literature. 18,19 We also found that the anti-S100 antibody stained a greater number of LCs than the anti-CD1a antibody.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, a reduction in these cells may not only contribute to the malignancy but may also allow for tumor progression. 16 Sikorski et al 17 reported that regression of cervical neoplasia may be associated with an increased number of LCs. In our study, the number of LCs in the existing lesion was directly proportional to the amount of these cells throughout the epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Although we could not achieve statistical significance, our findings correlate with the data presented by Ferluga et al [19] who demonstrated that the mean number of CD1a+ DC per mm 2 in laryngeal papilloma crosssections of patients exceeded the CD1a+ DC count in the specimens of patients with chronic laryngitis. A number of studies shows that DC density increases in tumor tissues during carcinoma progression as well as in HPV-infected epithelium [9][10][11][12]14,15]. On the other hand, some authors reported the decrease of DC count associated with HPV [13,16,17].…”
Section: Discussionmentioning
confidence: 98%
“…According to a number of studies, DC density in the tumor tissue correlates with a prognosis in many human neoplasms [9][10][11][12]. A number of researchers consider that HPV reduces the number of DC in infected tissue, some investigators believe that HPV infection is associated with an increased DC count, while others have found no changes in this parameter [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown low density of LCs in SCC of the skin 21 , uterine cervix 22 and anal mucosa 23 , and recent research on cervical SCC has suggested that the decreased density of LCs is secondary to low E-cadherin expression 21 . On the other hand, HPV increases the number of LCs in the anal mucosa of HIV-negative individuals 24 .…”
Section: Introductionmentioning
confidence: 99%